Implementation Of The Arabic Curriculum For The Purpose Of Special Academies In The Language Center Of The Ministry Of Defense - Awwaludin, Muhammad; Efendi, Ridwan (UIN Sunan Gunung Djati Bandung, 2022)
This research starts from a thought about the objectives of curriculum implementation related to the design of learning materials, curriculum implementation, learning plans, learning evaluations, and supporting and inhibiting factors on curriculum implementation at the Language center of the Ministry of Defense. This research uses a descriptive method case study research approach. The research begins to collect data and interpellate the research results with relevant explanations and supporting theories. The results obtained from this study show that the design of learning materials has a positive impact that is contrary to a percentage of 85% in student understanding and 15% which does not affect it, from the implementation of the curriculum applied 95% has a positive impact in supporting student understanding, in terms of learning evaluation carried out the understanding obtained by students reaches 95% and supporting factors achieved up to 95% and 50% inhibitions that come from students.